2019
DOI: 10.3934/microbiol.2019.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Microbial enzymes in the Mediterranean Sea: relationship with climate changes

Abstract: In most of the aquatic ecosystems, microorganisms are major players in the biogeochemical and nutrients cycles (Carbon Nitrogen, Phosphorus), through their enzymatic activities (leucine aminopeptidase, alkaline phosphatase and beta-glucosidase) on organic polymers such as polypeptides, organophosphate esters and polysaccharides, respectively. The small monomers released by decomposition are metabolised by microbes, supporting their growth. Most of the extracellular enzymes are adaptative and their synthesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 72 publications
(193 reference statements)
2
12
1
Order By: Relevance
“…The LAP/GLU ratio in our study was different from the ranges observed by Sala et al [ 14 ] in the Arctic ocean (85–100), and from temperate regions (as in the oligotrophic Mediterranean Sea) where LAP prevail over other enzymatic activities [ 13 , 46 ]. Nevertheless, a prevalence of GLU on LAP was observed in Arctic fjords [ 20 ], and this suggests that patterns of peptide hydrolysis may differ between temperate and high latitude sites [ 52 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The LAP/GLU ratio in our study was different from the ranges observed by Sala et al [ 14 ] in the Arctic ocean (85–100), and from temperate regions (as in the oligotrophic Mediterranean Sea) where LAP prevail over other enzymatic activities [ 13 , 46 ]. Nevertheless, a prevalence of GLU on LAP was observed in Arctic fjords [ 20 ], and this suggests that patterns of peptide hydrolysis may differ between temperate and high latitude sites [ 52 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, AP may be produced both by prokaryotes (bacteria and cyanobacteria) and eukaryotes (phyto- and zoo-plankton). Other organisms possess phosphoester hydrolases (phosphatases), able to release inorganic phosphorus for metabolic needs [ 46 ]. It has been demonstrated that phagotrophic nanofagellates and marine invertebrates might release extracellular enzymes through major physiological processes such as excretion or sloppy feeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these five studies the lowest substrate concentration used was 50 nM (typically the lower concentration in the set is between 1 and 5 µM), while the highest concentration was 1200 µM (the range of the higher concentrations in the set is 5-1200 µM, with a median of 200 µM). Another compilation of data from the Mediterranean Sea (Zaccone and Caruso, 2019) showed that 6 out of 22 studies used a single concentration (assumed to be saturating) with a median of 125 µM for leucine 7-amido-4-methyl coumarin and 50 µM for methylumbelliferyl-phosphate. Likewise, the remaining studies assessed enzyme kinetics with a highly variable range of substrate concentrations (lowest concentrations of 0.025-200 µM, with a median of 0.1 µM; highest concentrations of 1-4000 µM, with a median of 20 µM).…”
Section: Introductionmentioning
confidence: 99%